Analisis Promosi Penjualan Sepeda Motor Honda di Medan (Studi Kasus pada PT Daya Anugerah Motor) - Hutabarat, Fauzi Akbar Maulana; Nugroho, Ngajudin (BISMA Cendekia, 2020)
The aim of this research is to analyze the Sales Promotion at PT Daya Anugerah Motor, Medan. This research using a qualitative descriptive method. Data collection method by the interview and observation. Writer connecting to the result of the interview with Assauri (2013) theory about type of sales promotion, it can be concluded that the sales promotion type that applied in PT Daya Anugerah Motor Medan is: (1)Consumer Promotion trough free ride facility (consumer do a direct demonstration) with the motorcycle that they will be brought, marketers explain the features of the motorbike to the potential customer, give a discount for down payment fee and installment fee to a potential customer who will buy the product in this company; (2)Trade Promotion, the company provide incentives for agents following the product and selling unit according to the agreement between two-party; (3)SalesForce Promotion, provide an incentive for the marketers as Rp.100.000,- per sold unit, marketers who can sell more than  25 unit of the motorcycle in a month will be given additional incentive as Rp.500.000,-. Tour abord reward is given to the best marketers who can achieve a yearly target from the company.